Nexus between economy and environment: Greening India’s agriculture to combat climate change - A, YAZHINI; A, MALAISAMY; M, RASWANTHKRISHNA; M, BALASUBRAMANIAN; A, VIDHYAVATHI (The Indian Journal of Agricultural Sciences, 2025)
Climate change significantly affects various industries and economic sectors. It is primarily driven by greenhouse gas emissions, which result in global warming and cause shifts in climatic patterns, such as alterations in monsoon cycles and temperature changes. There are many studies related to emission, from secondary sector but the India's agricultural sector contributing 14% to the nation’s total emissions is less focused. The present study was carried out in 2024 at Tamil Nadu Agricultural University, Coimbatore, Tamil Nadu highlights the increasing focus on adopting environmental friendly agricultural practices to achieve SDG 13-Climate Action. It investigates the relationship between carbon emissions intensity (CEI) from India's agricultural production (GVA) and its economy (Trade-NE). Secondary data were sourced from the World Emission Clock, FAO Stat, and GHG platform for the period of 1993 to 2023 for India. The Tapio decoupling study on India's economic growth (Agricultural GDP) and agricultural GHG emissions reveals both negative and positive decoupling. Weak decoupling is most evident in situations where both agricultural GDP and greenhouse gas emissions increase simultaneously but the emissions growth rate is less than the growth rate of GDP. Using the structural vector auto regressive (SVAR) model, the paper illustrates that an immediate increase in CEI reduces the net export (NE) and GDP. Lowering CEI positively impacts the GVA, enhancing resilience to climate change and fostering sustainable growth in agricultural net exports. Sustainable practices like climate-smart agriculture, drip irrigation in paddy cultivation, carbon credit scheme should be focused. Prioritizing these measures is vital for India to meet its emissions reduction targets and to combat climate change.